2014
DOI: 10.1039/c4ra02341b
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated anthracene dendrimers with monomer-like fluorescence

Abstract: A series of highly fluorescent conjugated anthracene dendrimers having monomeric emission profile, but still exhibiting fast exciton depolarisation, are here presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…9-Bromo-10-phenylanthracene was synthesized according to the literature. 52 Preparation of 4-(10-phenylanthracene-9-yl)pyridine, 3. The title compound was synthesized as follows: 330 mg (0.99 mmol) of 9-bromo-10-phenylanthracene was added to a reaction vessel together with 201 mg (0.98 mmol) of 4-pyridine boronic acid pinacole ester and 27 mg (0.02 mmol, 2 mol%) of Pd(PPh 3 ) 4 .…”
Section: Synthesismentioning
confidence: 99%
“…9-Bromo-10-phenylanthracene was synthesized according to the literature. 52 Preparation of 4-(10-phenylanthracene-9-yl)pyridine, 3. The title compound was synthesized as follows: 330 mg (0.99 mmol) of 9-bromo-10-phenylanthracene was added to a reaction vessel together with 201 mg (0.98 mmol) of 4-pyridine boronic acid pinacole ester and 27 mg (0.02 mmol, 2 mol%) of Pd(PPh 3 ) 4 .…”
Section: Synthesismentioning
confidence: 99%
“…Here we demonstrate that by effectively extending the triplet lifetime of the ruthenium complex by coordination of the anthracene ligands, the upconversion quantum yield is increased threefold to 4.5% with complex RuOEP(CO)2. We have previously studied the properties of DPA based dendrimers and oligomers 45,62 and shown that intra-molecular TTA is possible in such structures. Combined with the current study, where efficient intra-molecular TET is achieved, we are en route to developing fully functioning, well defined, supramolecular TTA upconversion systems, with broad implications spanning solar energy harvesting devices to bioimaging and drug targeting.…”
Section: Resultsmentioning
confidence: 99%
“…Ligand design is based on our previous work with 9,10-diphenylanthracene (DPA) based ligands and dendrimeric structures. 25,45 Fig. 1 shows the structures of the ligands: ligand 1 has a metapyridine substitution, ligands 2-5 have para-pyridine substitutions with increasing bridge lengths and dendrimeric ligands 6 and 7 have an increasing number of DPA monomer units.…”
Section: Ligand Design and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Efficiency limits and maximal energy storage densities in molecular solar thermal materials is discussed (4,5) and new systems are being developed. (6)(7)(8) An overview of our research efforts to harness solar energy by developing a) efficient MOST and b) triplet-triplet annihilation photon upconversion systems (TTA-UC) will be presented. (1-9) Our work is both focused on development of new materials (1,(6)(7)(8) and the demonstration of their function in devices.…”
Section: Figure 1 Energy Diagram Explaining the Enthalpy Of Energy Smentioning
confidence: 99%